Role of cacao (Theobroma cacao L.) extracts in alveolar bone remodeling in diabetic rats during orthodontic tooth movements - Nuzulul Hikmah; Mohamad Hidayat; Nur Permatasari; Aulanni’am Aulanni’am; Achmad Rudijanto (Journal of Advanced Pharmaceutical Technology & Research)
Orthodontic tooth movement (OTM) in diabetes can increase alveolar bone resorption and decrease formation. Cacao beans contain several bioactive compounds that can increase osteoblast differentiation and mineralization and inhibit osteoclastogenesis to maintain tooth stability. We explored the role of cacao extracts on alveolar bone remodeling in diabetic rats during OTM. Cacao extracts were assayed for phytochemical screening and antioxidant capacity. Twenty-five rats were divided into nondiabetes, diabetes, diabetes cacao 125, diabetes cacao 250, and diabetes cacao 125 groups. Diabetes was induced by injecting the rats with streptozotocin for 5 days. An orthodontic device was inserted between the maxillary incisors, and cacao extract was administered orally. Furthermore, enzyme-linked immunosorbent assay methods were used to analyze bone alkaline phosphatase (BALP) and receptor activators of nuclear factor kappa-B ligand (RANKL) levels. Tartrate-resistant acid phosphatase (TRAP) expression was analyzed using immunohistochemical staining, and the osteoclast/osteoblast ratio was observed through hematoxylin–eosin staining. The data were analyzed using analysis of variance and post hoc tests, with P < 0.05 being statistically significant. Cacao extracts contained 7.27% phenolic, 0.02% flavonoid, 1.63% tannin content, and 147.47 µg/g of half-maximal inhibitory concentration. Approximately 250 mg/kg body weight of cacao extracts significantly increased BALP levels and decreased RANKL levels, TRAP expression, and osteoclast/osteoblast ratio in the diabetes group (P < 0.05). Cacao extracts can promote alveolar bone remodeling in diabetic rats during OTM by reducing alveolar bone resorption and increasing deposition.